(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In modern conditions, the organization of an internal audit service in a company allows the management of this company to provide the most transparent and reliable economic information on financial and economic activities for effective and accurate decision-making, a highly effective accounting system and prevention of violations, and confirmation of the objectivity and reliability of reports of structural units. , optimizes taxation.